Lecturers' Perception of Hybrid Metacognitive-Based Instruction in Teaching Critical Listening in Indonesian Higher Education Institution - Muhammad Safar Nur; Muhammad Basri; Sahril Sahril (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
This study explores lecturers’ perceptions of Hybrid Metacognitive-Based Instruction (HMBI) in teaching critical listening at an Indonesian higher education institution. Employing a qualitative descriptive design, data were collected from 10 lecturers through semi-structured interviews, questionnaires, and document analysis. The findings highlight the effectiveness of HMBI in fostering critical listening skills by integrating metacognitive strategies such as reflection, goal-setting, and self-regulation with hybrid tools, including podcasts and online discussions. Lecturers reported improvements in student autonomy, engagement, and analytical abilities, particularly in identifying implicit meanings and evaluating spoken content. However, challenges were identified, including technological barriers, time-intensive preparation, and initial student resistance to reflective practices. These obstacles underscore the need for institutional support, such as reliable technological infrastructure, professional development programs, and scaffolding strategies to ease the adoption of HMBI. The study emphasizes the potential of HMBI as a transformative approach to teaching critical listening, blending active learning principles with technological innovation to enhance higher-order cognitive skills. Recommendations include tailored strategies for gradual implementation and addressing digital divides to optimize its impact. The research contributes to the growing discourse on hybrid learning models and metacognitive instruction, offering practical insights for educators and institutions in diverse educational contexts.